DIATOM IDENTIFICATION IN NORTHERN TOWUTI LAKE USING SEISMIC INVERSION METHOD - Putri Oldia, Almira
Drilling is conducted in Towuti Lake (2,75o South Latitude; 121,5o East Longitude) to identify paleoclimate, history of the lake, and their effects on lake sediment. Drilling point is determined through 2D seismic survey to know where the thickest sediment is. One of the important characteristics lithologies in Towuti Lake is diatom which is which is very sensitive to climate. Moreover, diatoms were found in two wells located at different locations. This becomes interesting to study through the distribution of diatoms in the northern of the lake. The data used in this study are 2D seismic post-stack time migration and two wells. Lake seismic data are vulnerable to multiple. In addition, the available well data does not have density and checkshot, so pre-conditioning of seismic data and well data is carried out. Seismic surveys are carried out on various vintage, Lake Towuti sediments are classified as thin layer, two wells have different P-wave trends so spectral balancing method, P-wave trend modification, and Optimum Wiener Filter method is carried out to improve lateral resolution and continuity. Diatom distribution is obtained through seismic inversion method. Based on the analysis from pseudoResGR maps and isochron maps, there are autochthonous diatoms and allochthonous diatoms in Lake Towuti.